Hot-stage microscopy for determination of API fragmentation: comparison with other methods - Šimek, Michal; Grünwaldová, Veronika; Kratochvíl, Bohumil (Pharmaceutical development and technology, 2016)
Although the fragmentation of the active pharmaceutical ingredient (API) is a phenomenon that is mentioned in many literature sources, no well-suited analytical tools for its investigation are currently known. We used the hot-stage microscopy method, already presented in our previous work, and studied the real fragmentation of the tadalafil particles in model tablets which were prepared under different compaction pressures. The morphology, spectral imaging and evaluation of plastic and elastic energies were also analyzed to support the hot-stage method. The prepared blend of tadalafil and excipients was compacted under a several forces from 5 to 35 kN to reveal the trend of fragmentation. The exact fragmentation of tadalafil with increased compaction pressure was revealed by the hot-stage microscopic method and it was in good agreement with plastic and elastic energies. Conversely, spectral imaging, which is being used for this analysis, was considered to be inaccurate methodology as mainly agglomerates, not individual particles, were measured. The availability of the hot-stage microscopic method equips pharmaceutical scientists with an in vitro assessment technique that will more reliably determine the fragmentation of the API in finished tablets and the behavior of the particles when compacted.
Keywords: Hot Temperature; velikost částic; tablety; Tablets; particle size; vysoká teplota; Microscopy, Electron, Scanning; fragmentation; spectral imaging; API; tadalafil; Technology, Pharmaceutical; hot-stage microscopy; farmaceutická technologie; Particle Size; Tadalafil; mikroskopie elektronová rastrovací